Teachers’ Efforts to Stay Resilient during the Emergency Remote Teaching - Daniel Ginting (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
Education worldwide faces a daunting challenge following the closure of schools in response to the pandemic protocols. Many schools have switched to distance teaching to ensure the implementation of education for all students. ERT is meant to start a temporary shift in instructional delivery to an alternative teaching and learning delivery due to crisis conditions. This paper presents a sketch of teachers (Guru Penggerak) who have shared their experience during the emergency remote teaching. Although they had gone through their ERT quite well, they admitted that their teaching needed improvement. Some of their best teaching practices are presented as follows: enhancing professional development through trainings, establishing collaborative atmosphere through mentorship, taking initiatives to design learning materials independently, promoting commitment through favorable communication, and delivering materials in a measurable and scheduled manner. This paper provides several practical teaching pedagogic implications to enhance teachers’ professional development during the new normal.